CRITICAL ANALYSIS OF CHILDHOOD SANSKARAS (SACRAMENTS) IN LIGHT OF CONTEMPORARY SCIENCE - Deepshikha; Amit Kumar, Rai (International Journal of Ayurveda and Pharma Research, 2015)
India has a rich cultural heritage which affects the life of a person at all stages of life. Hinduism is one of the oldest world religions prevailing in Indian subcontinent. Hindu mythology describes various Sanskaras (sacraments/religious rites) outlined from birth to death of an individual. Out of the sixteen Sanskaras described, eight are for children. These are Jata Karma (birth rites), Namakaran (naming), Nishkraman (taking baby out of home), Annaprashan (starting solid feeding), Chudakarma (head shaving), Karnavedhana (piercing of the ear), Upanayan (thread ceremony) and Vedarambha (start of formal education). This article analyzed these Sanskaras in detail and gives a critical approach to their relevance in light of modern scientific knowledge. Though primarily considered as religious rites, they were significant in context of child health and provided opportunity for routine examination of child at regular intervals. Sanskara prepares one for the next stage of growth. A thorough review of childhood Sanskaras revealed that they were aimed at preparing the baby for extra uterine life successfully, developed proper feeding habits, ensured adequate nutrition, prevented diseases, adapted baby to environment for further survival, gave individual identity and educated the child. It took care of not only physical but also mental, social and spiritual development of child, thus made him a responsible youth of good character who proved to be an asset to the society. These sanskaras are apt till date and worth practicing in todays era.